2021
DOI: 10.4314/vulnew.v79i.3
|View full text |Cite
|
Sign up to set email alerts
|

Further observations and implications of Oil Palm Elaesis guineensis fruit consumption by Hooded Vultures Necrosyrtes monachus in coastal Gambia.

Abstract: No Abstarct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
10
1
Order By: Relevance
“…In unprotected areas, Claffey (1995) and F. Lemaire and B. Dowsett (data from 2009) inOgada and Buij (2011), reported that Hooded Vultures were frequently seen year-round in riparian areas in the Bétérou area. However, in the current study, surveying this area, we did not encounter any Hooded Vultures.The frequency of Hooded Vultures recorded during road counts in northern Benin was about four individuals per 100 km, which is very low, compared to 291, 255 and 734 individuals every 100 km recorded in recent surveys in Gambia(Barlow & Fulford, 2013;Henriques et al, 2018;Jallow et al, 2022). Interestingly, in neighbouring BurkinaFaso, a recent nationwide road count recorded 1365 Hooded Vultures over 2261 km, with an average of 60 individuals per 100 km (Daboné et al, 2024), which suggests there may have been a massive decline in Hooded Vulture populations in Benin.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…In unprotected areas, Claffey (1995) and F. Lemaire and B. Dowsett (data from 2009) inOgada and Buij (2011), reported that Hooded Vultures were frequently seen year-round in riparian areas in the Bétérou area. However, in the current study, surveying this area, we did not encounter any Hooded Vultures.The frequency of Hooded Vultures recorded during road counts in northern Benin was about four individuals per 100 km, which is very low, compared to 291, 255 and 734 individuals every 100 km recorded in recent surveys in Gambia(Barlow & Fulford, 2013;Henriques et al, 2018;Jallow et al, 2022). Interestingly, in neighbouring BurkinaFaso, a recent nationwide road count recorded 1365 Hooded Vultures over 2261 km, with an average of 60 individuals per 100 km (Daboné et al, 2024), which suggests there may have been a massive decline in Hooded Vulture populations in Benin.…”
contrasting
confidence: 53%
“…In contrast, in central Burkina Faso, Banjul, the coastal and Western regions of The Gambia, the Ziguinchor department of southwestern Senegal, Guinea-Bissau and the southern region of Ghana, Hooded Vultures are reportedly still abundant (Annorbah & Holbech, 2012;Barlow, 2012;Barlow & Fulford, 2013;Gbogbo & Awotwe-Pratt, 2008;Henriques et al, 2017;Jallow et al, 2016Jallow et al, , 2022Mullié et al, 2017;Smalley, 2016;Thiollay, 2006b). This gave rise to a discussion forum about possibly downlisting the status of the Hooded Vulture to Endangered on the IUCN Red List of Threatened Species (D. Ogada, pers.…”
Section: Introductionmentioning
confidence: 99%
“…600 km 2 or 4-5% of the currently estimated global population, an area that represents less than 0.0001% of the species' range (Jallow et al 2016). Therefore, elevated competition for food due to high densities of conspecifics is a probable driver of the exploration and exploitation of such a varied list of food resources discussed here and previously (Barlow 2020, Barlow et al 2021. We have shown that the study area presents a wide range of scavenging possibilities that are mostly created by anthropogenic activity.…”
Section: Discussionmentioning
confidence: 63%
“…We have demonstrated the importance of ocean beaches and fish landing sites in south Gambia and in southern Senegal for scavenging by Hooded Vultures, while knowledge of coastal beach feeding is lacking elsewhere in the species' range (Barlow et al 2021). We have also updated the evidence relating to the consumption of African Oil Palm Elaeis guineensis fruit by Hooded Vultures, another feeding habit which remains undocumented elsewhere (Barlow 2020).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation